Adaptive number knowledge and its relation to arithmetic and pre-algebra knowledge. (June 2017) - McMullen, Jake; Brezovszky, Boglárka; Hannula-Sormunen, Minna M.; Veermans, Koen; Rodríguez-Aflecht, Gabriela; Pongsakdi, Nonmanut; Lehtinen, Erno
Abstract: Traditionally measured skills with arithmetic are not related to later algebra success at levels that would be expected given the close conceptual relation between arithmetic and algebra. However, adaptivity with arithmetic may be one aspect of arithmetic competences that can account for additional variation in algebra attainment. With this in mind, the present study aims to present evidence for the existence and relevance of a newly acknowledged component of adaptivity with arithmetic, namely, adaptive number knowledge. In particular, we aim to examine whether there are substantial individual differences in adaptive number knowledge and to what extent these differences are related to arithmetic and pre-algebra skills and knowledge. Adaptive number knowledge is defined as the well-connected knowledge of numerical characteristics and relations. A large sample of 1065 Finnish late primary school students completed measures of adaptive number knowledge, arithmetic conceptual knowledge, and arithmetic fluency. Three months later they completed a measure of pre-algebra skills. Substantial individual differences in adaptive number knowledge were identified using latent profile analysis. The identified profiles were related to concurrent arithmetic skills and knowledge. As well, adaptive number knowledge was found to predict later pre-algebra skills, even after taking into account arithmetic conceptual knowledge and arithmetic fluency. These results suggest that adaptive number knowledge is a relevant component of mathematical development, and may help account for disparities in algebra development. Highlights: Adaptive Number Knowledge (ANK) may be important for math development. ANK is presumed to underlie adaptivity with arithmetic problem solving. Individual differences in primary school students were found using latent profile analysis. ANK was related to arithmetic fluency and conceptual knowledge of arithmetic. ANK was related to pre-algebra knowledge.